Possibilidades de uso do site de rede social Youtube na educação básica em Itabaiana-SE - Mota, Gersivalda Mendonça da (2018)
In today's scenario of changes in society and in people's daily lives, we understand that these changes must also happen in the educational space. It has been found that many platforms and technological devices are available for educational use, among them YouTube, a social networking site that shares videos produced by different people. Thus, this research was designed to answer the question about the possibilities of using the social networking site Youtube in basic education. Its objective was to investigate the possibilities of using the social networking site Youtube with teachers of basic education in the municipality of Itabaiana, in Sergipe. To meet this demand, we sought to discuss the possibilities of using the Youtube social networking site in basic education, through a proposal to create and co-create videos with teachers through a training course. The work was based on the methodology of Research-training, used by it to be situated in a perspective of commitment and of implication of the researchers with their practices, allowing individual and / or collective changes. Through this methodology, an authorial training device was developed, the workshop entitled "Possibilities of using the Youtube social network in education", with a total workload of forty hours. In this workshop, it was possible to share knowledge about the possibilities of Youtube in the learning process, in addition to proposing the development of a channel so that teacher could produce and share on the internet videos with their students. In order to collect data from this research, we used as a technique the application of a questionnaire to know the profile of teachers, observation of teachers in the school space, production of research diaries and participant observation of the activities developed during the workshop. It was observed that teachers knew and even used the site in their classes, but just like any other didactic material, that is, to reproduce the information, leaving aside the possibility of being the author or co-author of new productions more related to their reality and its culture. As a result of the workshop offered, the participating teachers co-produced videos and culminated in school to socialize with the school community their productions, but not everyone was able to make available on the Youtube channel the productions made. We realize that non-sharing on Youtube is related to two factors: lack of immersion of teachers in cyberculture, regarding the use of this culture in education, and availability to carry out ongoing teacher training activities. Educational policies, whether at the municipal, state or federal level, have not contributed to the fact that teachers have, during their work hours, moments of continuous formation. In this way, the use of digital technologies in the classroom becomes increasingly distant from happening, because for the effective use of these technologies in education it is necessary a continuous training that goes beyond simple training or punctual capabilities.